Mechanical performance evaluation of the CFETR central solenoid model coil design. (23rd November 2017) - Liu, Xiaogang; Wang, Zhaoliang; Ren, Yong; Li, Junjun; Yin, Dapeng; Li, Lei; Gao, Xiang; Wu, Yu
Abstract: The Chinese Fusion Engineering Test Reactor (CFETR) Central Solenoid Model Coil is being fabricated by the Institute of Plasma Physics Chinese Academy of Sciences. The Model Coil is comprised of Nb3 Sn and NbTi modules held together by a preload structure. It will operate at 4.5 K to produce a peak field of 12 T at 48 kA. In order to investigate the feasibility and integrity of the Model Coil design before its manufacturing, the mechanical performance has been evaluated for the room temperature preload, 4.5 K stand-by and 48 kA operating conditions. A 1/15 3D detailed model that consists of jackets, insulations, bladders, buffers and preload structure, is constructed and simulated using the coupled structural-thermal-electromagnetic solver of ANSYS. In contrary to a smeared winding pack model, our analysis with the detailed model can directly and precisely simulate the differential thermal contraction effect of the preload structure, jacket and insulations, as well as the electromagnetic load acting on the jacket. The detailed deformation and stress behaviors of the Model Coil are illustrated and discussed. The results indicate that the final design of the CFETR Central Solenoid Model Coil is reasonably conservative and satisfy the design criteria.